The Relationship between Russia and the European Populist Far Right: Motivations and Political Use (قضايا سياسية, 2023)
The research reviews the historical roots of the relations, coordination and cooperation between the Russian Federation and the extreme populist right-wing parties, and the motives and goals of the two parties in this relationship, which began to take an upward pattern from the early nineties of the twentieth century. The relations between the two were not limited to a specific aspect but had multiple aspects and patterns of political, partisan, media and financial cooperation in order to achieve the main goals and objectives of this relationship, being addressing the repercussions of globalization and the attempt to dismantle the European Union and NATO, in addition to gaining support and legitimacy for Russian policies that do not enjoy European and international support. Also, the two sides seek to mitigate the effects of European and American sanctions on Russia, and influence European policies within the institutions of the European Union and European countries. Further, this paper traces the impacts of the Russian-far right parties relations on the European political landscape.